ESTIMATION OF FISH PRODUCTION AROUND INDONESIA ARCHIPELAGO USING SATELLITE DATA - ANAK AGUNG AYU PUTRININGSIH; Takahiro Osawa; I WAYAN REDI ARYANTA (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2011)
Indonesia as an archipelagic country has the potentiality of a huge fishery resources and high biodiversity. Fishresources in the waters can be estimated by knowing the content of the primary production (PP) of these waters.The aim of the research are to estimate the variability of environment parameter (SST and Chl-a concentration)and to estimate of PP and fish production (FP), derived from satellite around Indonesia Archipelago.The research was conducted in nine of Indonesia Fisheries Management Area from 2004 to 2006. The PPwas calculated by Vertically Generalized Production Model (VGPM), which was introduced by Behrenfeld andFalkowski (1997a). The model introduced by Pauly and Christensen (1995) calculated the FP. The estimationof FP from model was compared to the FP data from the Department of Marine and Fisheries Resources ofIndonesia.In the territorial waters of Indonesia Archipelago the highest variations of average SST and Chl-a was estimatedat Arafuru Sea, whereas the lowest variation was estimated at Sulawesi Sea and Pacific Ocean. The total annualfish production from the model showed the highest and the lowest values were estimated at Indian Ocean(1,614,135.44 tons) and Malacca Strait (268,305.64 tons), respectively. On the other hand, the total annualfish production from Department of Marine and Fisheries Resources of Indonesia showed the highest and thelowest values were estimated at Java Sea (850,151 tons) and Banda Sea (198,078 tons), respectively. The highestcorrelation between fish production from satellite data and the data from Department of Marine and FisheriesResources of Indonesia was found at Arafuru Sea with R = 0.97. The nine fisheries areas of Indonesia during2004 to 2006 were categorized as fully until over exploited fishing zone.